Lck, Membrane Microdomains, and TCR Triggering Machinery: Defining the New Rules of Engagement - Filipp, Dominik; Ballek, Ondřej; Manning, Jasper (Frontiers in Immunology, 2012)
In spite of a comprehensive understanding of the schematics of T cell receptor (TCR) signaling, the mechanisms regulating compartmentalization of signaling molecules, their transient interactions and rearrangement of membrane structures initiated upon TCR engagement remain an outstanding problem. These gaps in our knowledge are exemplified by recent data demonstrating that TCR triggering is largely dependent on a preactivated pool of Lck concentrated in T cells in a specific type of membrane microdomains. Our current model posits that in resting T cells all critical components of TCR triggering machinery including TCR/CD3, Lck, Fyn, CD45, PAG and LAT are associated with distinct types of lipid-based microdomains which represent the smallest structural and functional units of membrane confinement able to negatively control enzymatic activities and substrate availability that is required for the initiation of TCR signaling. In addition, the microdomains based segregation spatially limits the interaction of components of TCR triggering machinery prior to the onset of TCR signaling and allows their rapid communication and signal amplification after TCR engagement, via the process of their coalescence. Microdomains mediated compartmentalization thus represents an essential membrane organizing principle in resting T cells. The integration of these structural and functional aspects of signaling into a unified model of TCR triggering will require a deeper understanding of membrane biology, novel interdisciplinary approaches and the generation of specific reagents. We believe that the fully integrated model of TCR signaling must be based on membrane structural network which provides a proper environment for regulatory processes controlling the TCR triggering.